RADI-11. NRG ONCOLOGY CC001: A PHASE III TRIAL OF HIPPOCAMPAL AVOIDANCE IN ADDITION TO WHOLE-BRAIN RADIOTHERAPY (WBRT) PLUS MEMANTINE TO PRESERVE NEUROCOGNITIVE FUNCTION IN PATIENTS WITH BRAIN METASTASES (BM). (12th August 2019) - Tomé, Wolfgang; Deshmukh, Snehal; Gondi, Vinai; Brown, Paul; Wefel, Jeffery; Armstrong, Terri; Bruner, Deborah; Bovi, Joseph; Robinson, Clifford; Khuntia, Deepak; Grosshans, David; Konski, Andre; et al.
Abstract: BACKGROUND: NRG CC001, a phase III trial of WBRT+memantine (WBRT+M) with or without Hippocampal Avoidance (HA), sought to assess the neuro-protective effects of lowering the radiation dose received by the hippocampus. METHODS: Patients (pts) with brain metastases were stratified by RPA class and prior radiosurgery/surgery and randomized to either WBRT+M or HA-WBRT+M (30Gy/10 fractions). Standardized neurocognitive function (NCF) tests were performed at baseline, 2, 4, 6, and 12 months (mos.). The primary endpoint was NCF failure, defined as decline using the reliable change index on Hopkins Verbal Learning Test-Revised, Trail Making Test, or Controlled Oral Word Association. Cumulative incidence estimated NCF failure (death without NCF failure was competing risk); between-arms differences tested using Gray's test. Deterioration at each collection time point was tested using a chi-square test. Patient-reported symptoms were assessed using the MD Anderson Symptom Inventory with Brain Tumor module and analyzed using mixed effects models and t-tests. RESULTS: From 7/2016 to 3/2018, 518 patients were randomized. Median follow-up was 7.9 mos. HA-WBRT+M was associated with lower NCF failure risk (adjusted HR=0.74, p=0.02) due to lower risk of deterioration in executive function at 4 mos. (p=0.01); and encoding (p=0.049) and consolidation (p=0.02) at 6 mos. Age≤61 predicted for lower NCF failure risk (HR=0.60, p=0.0002); non-significant test for interaction indicated independent effects of HA and age. Patient-reported fatigue (p=0.036); difficulty speaking (p=0.049); and problems remembering things (p=0.013) at 6 mos. favored the HA-WBRT+M arm. Imputation models accounting for missing data also favored the HA-WBRT+M arm for patient-reported cognition (p=0.011) and symptom interference (p=0.008) at 6 mos. Treatment arms did not significantly differ in toxicity; intracranial progression or overall survival. CONCLUSIONS: While achieving similar intracranial control and survival; Hippocampal Avoidance during WBRT+M for brain metastases better preserves NCF and patient-reported symptoms. Supported by UG1CA189867 (NCORP) and DCP from the NCI.